METHOD DEVELOPMENT OF KUERSITRIN ENRICHMENT FROM ASTHMA-PLANT (EUPHORBIA HIRTA L.) USING AROMATIC MACROPOROUS RESIN - Sidik Ode Ishak, Sumail
Asthma-plant contains high amount of kuersitrin flavonoids so it is potential as a new source of flavonoids. This research’s objective is to develop the method of kuersitrin’s enrichment by using macroporous resin, which is known to be safer, eco-friendly, economics, and efficient. Evaluations were conducted over performance characteristics and separation of macroporous resin in respect to kuersitrin’s enrichment and the adsorption and desorption of the macroporous resin in respect to kuersitrin. Result shows the process of macroporous resin’s adsorption and desorption in respect to the amount of kuersitrin in the extract was following first order model which means the process of adsorption is not affected by the other compounds. The examination of the isothermic adsorption shows a congruence to Freundlich’s model (R2= 0.9850) than Langmuir’s (R2= 0.4334). On the optimal condition, the enrichment of kuersitrin by using macroporous resin increased the purity and content to 4.72 times which was from 3.60% in the extract to 17.02% by percentage of recovery as 50.39%.